Q. 1 B4.3( 16 Votes )

<span lang="EN-US

Answer :

2x2 + x - 6 = 0

2x2 + 4x - 3x - 6 = 0


2x(x + 2) 3(x + 2) = 0


(2x - 3)(x + 2) = 0


The roots of the equation are those value for which (x + 2) (2x - 3) = 0




Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics